VD_FINDINFO HC / 2021 / 167 vom 10. März 2021 - VD Tribunal cantonal (2021)
BAIL À LOYER, RÉSILIATION, CONDITION DE RECEVABILITÉ, DÉCISION D'IRRECEVABILITÉ, SOUS-LOCATION | 138 CPC (CH), 140 CPC (CH), 148 CPC (CH), 59 al. 1 CPC (CH)